Electrifying mobility : realising a sustainable future for the car - Parkhurst, Graham; Clayton, William (Transport and sustainability ;, 2022)
Transport is responsible for a growing share of global energy consumption and greenhouse gas emissions, emerging as an economic sector for which technical solutions have shown limited benefits and a shift to electric mobility is seen as an essential part of tackling both problems. However, despite electric motive power being older technology than internal combustion engines and having many advantages, both inherent disadvantages and the inertia of not being the dominant road transport technology mean that it is only recently that electric vehicles (EVs) have attracted serious policy attention. Electrifying Mobility: Realising a Sustainable Future for the Car examines the basis of this electric mobility 'turn', considering the drivers, barriers to adoption and the current lived experience of EV use, drawing upon this experience to inform planning for mass EV adoption and how regulation might change to reflect the specific needs and challenges raised. Considering future transport policy, practice, and management where EVs become an important part of the road transport fleet, and, it is assumed, eventually come to dominate it, chapters study how EV and Connected and Autonomous Vehicle (CAV) technologies relate, and whether there are synergies with shared mobility. The Transport and Sustainability series addresses the important nexus between transport and sustainability containing volumes dealing with a wide range of issues relating to transport, its impact in economic, social, and environmental spheres, and its interaction with other policy sectors.